Decentralized clinical trials (DCTs): A few ethical considerations - Carlo Petrini; Chiara Mannelli; Luciana Riva; Sabina Gainotti; Gualberto Gussoni (Frontiers Media S.A., 2022)
Decentralized clinical trials (DCTs) are studies in which the need for patients to physically access hospital-based trial sites is reduced or eliminated. The CoViD-19 pandemic has caused a significant increase in DCT: a survey shows that 76% of pharmaceutical companies, device manufacturers, and Contract Research Organizations adopted decentralized techniques during the early phase of the pandemic. The implementation of DCTs relies on the use of digital tools such as e-consent, apps, wearable devices, Electronic Patient-Reported Outcomes (ePRO), telemedicine, as well as on moving trial activities to the patient's home (e.g., drug delivery) or to local healthcare settings (i.e., community-based diagnosis and care facilities). DCTs adapt to patients' routines, allow patients to participate regardless of where they live by removing logistical barriers, offer better access to the study and the investigational product, and permit the inclusion of more diverse and more representative populations. The feasibility and quality of DCTs depends on several requirements including dedicated infrastructures and staff, an adequate regulatory framework, and partnerships between research sites, patients and sponsors. The evaluation of Ethics Committees (ECs) is crucial to the process of innovating and digitalizing clinical trials: adequate assessment tools and a suitable regulatory framework are needed for evaluation by ECs. DCTs also raise issues, many of which are of considerable ethical significance. These include the implications for the relationship between patients and healthcare staff, for the social dimension of the patient, for data integrity (at the source, during transmission, in the analysis phase), for personal data protection, and for the possible risks to health and safety. Despite their considerable growth, DCTs have only received little attention from bioethicists. This paper offers a review on some ethical implications and requirements of DCTs in order to encourage further ethical reflection on this rapidly emerging field.